MAHMUDXO‘JA BEHBUDIY “PADARKUSH” ASARINING YOSHLAR TARBIYASIGA TARBIYAVIY TA’SIRI - Nyutonova, X.L. (SCIENCE and SOCIETY, 2024)
This article analyzes the drama “Padarkush” by Mahmudhoja Behbudi,one of the great representatives of Jadid literature.The artistic images in it are explained. Contrasted with our present-day oriental customs.